2002
DOI: 10.1093/emboj/21.11.2526
|View full text |Cite
|
Sign up to set email alerts
|

The Toxoplasma gondii protein MIC3 requires pro-peptide cleavage and dimerization to function as adhesin

Abstract: Attachment and invasion of host cells by apicomplexan parasites involve the exocytosis of the micronemal proteins (MICs). Most MICs are adhesins, which show homology with adhesive domains from higher eukaryote proteins and undergo proteolytic processing of unknown biological signi®cance during their transport to micronemes. In Toxoplasma gondii, the micronemal homodimeric protein MIC3 is a potent adhesin that displays features shared by most Apicomplexa MICs. We have developed an original MIC3-binding assay by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 26 publications
1
65
0
Order By: Relevance
“…The majority of micronemal proteins characterized to date form complexes that are important for proper cellular trafficking and secretion (13,23,24,26). For example, soluble microneme proteins such as MIC1 and MIC4 require interaction with the membrane bound protein MIC6 to ensure proper targeting to the micronemes (24).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of micronemal proteins characterized to date form complexes that are important for proper cellular trafficking and secretion (13,23,24,26). For example, soluble microneme proteins such as MIC1 and MIC4 require interaction with the membrane bound protein MIC6 to ensure proper targeting to the micronemes (24).…”
Section: Discussionmentioning
confidence: 99%
“…Although more than one-half of the known microneme proteins are processed by removal of an Nterminal or internal propeptide, little is known about the functions of these transient elements in the Apicomplexa (Brydges et al, 2000;Donahue et al, 2000;Cerede et al, 2001;Miller et al, 2001;Rabenau et al, 2001;Reiss et al, 2001;Harper et al, 2004b showed that the propeptide of TgMIC3 plays a regulatory role in masking lectin activity (Cerede et al, 2002), additional functions for protein maturation remain untested. The lack of sequence conservation among microneme propeptides suggests that they may fulfill additional roles beyond masking adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the phylum Apicomplexa, T. gondii features a distinct apical complex consisting of three types of secretory organelles. Regulated secretion of proteins from the apical micronemes is required for host cell invasion by providing adhesive protein complexes that bind receptors on the host cell surface (Fourmaux et al, 1996;Cerede et al, 2002;Harper et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important member of the MIC family, MIC8 participates in T. gondii invasion through interaction with soluble MIC3 (Cérède et al, 2002;Kessler et al, 2008), and is a potential vaccine candidate against acute and chronic T. gondii infections in a mouse model (Liu et al, 2010;Li et al, 2014). To investigate the genetic diversity of the MIC8 gene, 16 T. gondii strains from different hosts and geographical locations, and two reference isolates were examined in this study.…”
Section: Introductionmentioning
confidence: 99%